2011
DOI: 10.1371/journal.pone.0024440
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Severity of 2009 Pandemic Influenza A H1N1 in Taiwan

Abstract: BackgroundThis study is to determine the seroprevalence of the pandemic influenza A H1N1 virus (pH1N1) in Taiwan before and after the 2009 pandemic, and to estimate the relative severity of pH1N1 infections among different age groups.Methodology/Principal FindingsA total of 1544 and 1558 random serum samples were collected from the general population in Taiwan in 2007 and 2010, respectively. Seropositivity was defined by a hemagglutination inhibition titer to pH1N1 (A/Taiwan/126/09) ≥1:40. The seropositivity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
2
19
1
Order By: Relevance
“…In this study, cases of pH1N1 were detected in At the emergence of pandemic (H1N1) in 2009, the mean age of infected patients was 19 years, which correlates with other studies that have reported that pH1N1, in contrast to seasonal influenza, specifically targets younger age groups [11,12]. This may be explained by the fact that older adults have developed some level of protective antibody against pH1N1 due to previous infection with the related H1N1 virus [13].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, cases of pH1N1 were detected in At the emergence of pandemic (H1N1) in 2009, the mean age of infected patients was 19 years, which correlates with other studies that have reported that pH1N1, in contrast to seasonal influenza, specifically targets younger age groups [11,12]. This may be explained by the fact that older adults have developed some level of protective antibody against pH1N1 due to previous infection with the related H1N1 virus [13].…”
Section: Discussionsupporting
confidence: 86%
“…These results are consistent with those reported in Ontario (33.3z) (22) and Pittsburgh (40z) (28), which showed a higher seropositive rate in the AE60 years age group at the end of the influenza season and October 2010. However, the results were discordant with those of reports from Taiwan (11.8z) (18) and Greece (14.4z) (23) that were carried out in September and June 2010. Overall, the study showed that the highest percentage of individuals with antibodies to A(H1N1)pdm09 were children.…”
Section: Discussionsupporting
confidence: 45%
“…Taiwan also had 2 intense epidemics during the 2009 pandemic in August-September and in December (26). The epidemic curves for Okinawa were more similar to those for Taiwan than to those for mainland Japan.…”
Section: Discussionmentioning
confidence: 81%